Goal orientations, perceived motivational climate, and motivational outcomes in football: A comparison between training and competition contexts - van de Pol, P. K. C.; Kavussanu, M.; Ring, C. (Psychology of Sport and Exercise, 2012)
Objectives: In this study, we examined (a) variability and (b) differences in football players` goal orientations and perceptions of the motivational climate across training and competition contexts, and (c) whether the context moderates the relationships between goal orientations, motivational climate, and effort, enjoyment and tension. Design: Cross-sectional. Method: Football players (362 males and 48 females) completed questionnaires measuring goal orientations, perceived motivational climate, effort, enjoyment, and tension in training and competition. Results: Multilevel analysis revealed that the context explained significant variation in goals and climate perceptions beyond the athlete and team levels: Participants reported higher ego orientation and perceptions of performance climate in competition than in training, whereas task orientation and perceived mastery climate did not differ between the two contexts. Effort and enjoyment were both positively related to task orientation and unrelated to ego orientation in both contexts. Effort was positively associated with perceived mastery climate only in training, while enjoyment was positively associated with mastery climate in both contexts but more strongly in training than in competition. Effort was negatively associated with performance climate in both contexts. Tension was unrelated to task orientation. It was also inversely associated with ego orientation in training and unrelated to this goal in competition. Tension was unrelated to perceived mastery climate and positively related to performance climate but only in training. Conclusion: The findings highlight the importance of distinguishing between the training and competition contexts when examining achievement motivation in sport.